Fungsi-fungsi nilai budaya lokal pada organisasi publik - Syamsir Torang (Faculty of Social and Political Science, Universitas Airlangga, 2016)
Public organization is the government instrument which has role system, flow activities, and pattern of team work relation; it involves civil servants to serve the public. The objective of this study is to analysis the functions of local culture in the Centre General Hospital of Wahidin Sudirohusodo Makassar as public organization. This study is a qualitative research which applies as a case study approach. The data sources are primer and secondary data. The primer data was collected through observation of social situation (place, actor, and activity) and structured interview of the informants. The secondary data was collected through documentations. The technique of data analysis was performed through data collection, data reduction, data display and conclusion. The indicators of the study are functions (social identity, social cohesion, sense-making and control mechanism, motivation source, and inspiration source) of the local culture value (sipakatau). Sipakatau is the Bugenese language that means to appreciate and respect each other. This value has been espoused by Bugenese and Makassarise in applying their activities. The result of the study indicates that local culture value (sipakatau) has been functioned as social identity, social cohesion, sense-making and control mechanism, motivation source, and inspiration source by the Centre General Hospital of Wahidin Sudirohusodo Makassar.